Description of Student Academic Anxiety Level III Sidoarjo D3 Nursing Program Health Polytechnic Ministry of Health Surabaya - Suryadianto, Sabrina Aulia; Sulystiono, Dony; Maziyah, Alfi (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2024)
WHO research results in 2019 show that depression and anxiety cause loss global economy of 1 trillion USD each the year consequence loss productivity resource human. Worry is feeling No easy, worried, all at once scared the research design used in research This is research